Novel black yeast-like species in chaetothyriales with ant-associated life styles. Issue 4 (April 2021) - Quan, Yu; Ahmed, Sarah A.; Menezes da Silva, Nickolas; Al-Hatmi, Abdullah M.S.; Mayer, Veronika E.; Deng, Shuwen; Kang, Yingqian; Sybren de Hoog, G.; Shi, Dongmei
Abstract: Among ancestral fungi in Chaetothyriales, several groups have a life style in association with tropical ants, either in domatia or in carton-nests. In the present study, two strains collected from ant carton in Thailand and Malaysia were found to represent hitherto undescribed species. Morphological, physiological, phylogenetic data and basic genome information are provided for their classification. Because of the relatively large phylogenetic distances with known species confirmed by overall genome data, large subunit (LSU) and Internal Transcribed Spacer (ITS) ribosomal DNA sequences were sufficient for taxonomic circumscription of the species. The analyzed strains clustered with high statistical support as a clade in the family Trichomeriaceae. Morphologically they were rather similar, lacking sporulation in vitro . In conclusion, Incumbomyces delicatus and Incumbomyces lentus were described as new species based on morphological, physiological and phylogenetic analysis.